Decision Making for Complex Product and Process Development Using PLM - Viswanathan, Varun (2013)
Product Lifecycle Management (PLM) has a long history and it has evolved into a very advanced product and process management tool. It is used in the management of services too. The dissertation is based on the effective decision making using PLM. During the management of a product across its lifecycle, there will be many instances at which crucial decisions have to be made. The process of effective collaboration makes this process easier and efficient. The engineering change management integrates all the sections of a firm, so as to reach an effective consensus. The dissertation is also intended to carry out research on the current scenario of PLM systems and analyse the problems to which recommendations are provided.